Communication in the time of Covid- 19 - Samridhi Mishra, Dr. Pradnya V. Chitrao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Do you think Covid-19 pandemic has changed the way we communicate? Our relation with voice and video calls has been changing in this new normal world. People have now been connecting in new ways and have started hosting virtual meets and virtual reunions with friends they have not met for decades. Education in this virtual era has also changed - the way we communicate with the instructors or facilities. The communication has not just changed with the corporate companies but the change in communication can also be observed in the education sector, in shops, in government facilities and even in the hospitals. Even though there was a presence of the online communication tools before the covid-19 pandemic, the use of these tools has increased exponentially in the recent days. This paper studies and examines the various ways of communication, have people adopted the new communication and the explains the future of communication in this virtual world.